Controllable synthesis of transition metal nitride materials and performance tuning in photocatalysis and piezoelectric catalysis - Cheng, Zhixing (2021)
Energy crisis has become imminent owing to the increasing energy demand in recent years. Renewable and sustainable alternative energy resources, such as hydrogen have attracted significant attentions. In order to produce hydrogen energy efficiently, artificial photocatalysis is an attractive way forward. Use of piezoelectric materials for solar energy conversion is being researched in this context. However, such materials that are semiconductor-based are not practically viable applications. Simultaneously, as a kind of most efficient catalyst, the noble metal is difficult to apply in large-scale. Transition metal nitrides (TMNs) have become a family of alternatives of noble metal catalysts due to their unique properties. However, the present synthesis methodologies of TMNs are complex with severe conditions. Maintenance of morphology of TMNs also remains a challenge, since morphological changes do influence their activity. This thesis has provided a new strategy for production of TMNs with stable nano-morphology. These have been used for photocatalytic and piezoelectric H2 evolution, while discussing the structure-activity relationship. The details are listed below: